The Incidence and Risk of Herpes Zoster in Patients With Sleep Disorders: A Population-Based Cohort Study - Chung, Wei-Sheng (Medicine (Baltimore), 2016)
Lack of sleep can compromise the immune system, which may reactivate latent varicella-zoster virus. Studies on sleep disorders and the risk of herpes zoster (HZ) are scant. We conducted a population-based cohort study to evaluate the risk of HZ in patients with sleep disorders and potential risk factors for HZ development. We identified patients with sleep disorders without apnea from 2002 to 2005 by using the Taiwan Longitudinal Health Insurance Database. The patients without sleep disorders were randomly selected and frequency matched with patients with sleep disorders according to age, sex, and index year. We estimated the follow-up time in person-years for the patients from the entry date until HZ diagnosis, loss to follow-up, or the end of 2010. We used Cox proportional hazards regression models and a sensitivity analysis to estimate the risk of HZ while controlling for demographic characteristics and comorbidities. A total of 131,001 study participants (follow-up, 948,177 person-years; mean age, 51.2 ± 16.5 years; 62.2% women) were included in the study. Patients with sleep disorders exhibited a higher incidence of HZ compared with a comparison cohort when stratified by age, sex, and comorbidities. After adjustment for covariates, the sleep disorder cohort exhibited a 1.23-fold greater risk of HZ compared with the comparison cohort (95% confidence interval [CI] = 1.17–1.30). The incidence of HZ increased with age. Adults ages 65 years and older exhibited a 6.11-fold greater risk of HZ development compared with their younger counterparts (95% CI = 5.34–7.00). Cancers and autoimmune diseases were independent risk factors of HZ development. The patients with sleep disorders may carry an increased risk of developing HZ.